2018
DOI: 10.3847/1538-3881/aadcfc
|View full text |Cite
|
Sign up to set email alerts
|

Transiting Exoplanet Monitoring Project (TEMP). I. Refined System Parameters and Transit Timing Variations of HAT-P-29b

Abstract: We report the photometry of six transits of the hot Jupiter HAT-P-29b obtained from 2013 October to 2015 January. We analyze the new light curves, in combination with the published photometric, and Doppler velocimetric, and spectroscopic measurements, finding an updated orbital ephemeris for the HAT-P-29 system, T C [0] = 2456170.5494(15) [BJD TDB ] and P = 5.723390(13) days. It is 17.63 s (4.0 σ) longer than the previously published value, amounting to errors exceeding 2.5 hrs at the time of writing (on UTC 2… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…While the primary focus of MINERVA-Australis will be the radial velocity follow-up of transiting planet candidates found by TESS, five secondary photometric science goals include: photometric follow-up of TESS and other transit survey planets to ensure that the ephemerides are up-to-date and accurate for future followup observations (e.g., Hoyer et al 2016;Wang et al 2018b), ruling out potential false positives from nearby eclipsing binaries (Collins et al 2018;Ziegler et al 2018), searching for transit timing variations (Malavolta et al 2017;Saad-Olivera et al 2017) and longer-period planets (e.g., Otor et al 2016;Almenara et al 2018) and follow-up of planets found by radial velocity observations from the AAPS (e.g., Tinney et al 2011;Wittenmyer et al 2014). In addition, target-of-opportunity observations of high-priority solar system occultation events (e.g., Sicardy et al 2011a;Ortiz et al 2012Ortiz et al , 2017 are also planned using a very high-cadence camera that will be installed at a future date.…”
Section: First Science Results With Minerva-australismentioning
confidence: 99%
See 1 more Smart Citation
“…While the primary focus of MINERVA-Australis will be the radial velocity follow-up of transiting planet candidates found by TESS, five secondary photometric science goals include: photometric follow-up of TESS and other transit survey planets to ensure that the ephemerides are up-to-date and accurate for future followup observations (e.g., Hoyer et al 2016;Wang et al 2018b), ruling out potential false positives from nearby eclipsing binaries (Collins et al 2018;Ziegler et al 2018), searching for transit timing variations (Malavolta et al 2017;Saad-Olivera et al 2017) and longer-period planets (e.g., Otor et al 2016;Almenara et al 2018) and follow-up of planets found by radial velocity observations from the AAPS (e.g., Tinney et al 2011;Wittenmyer et al 2014). In addition, target-of-opportunity observations of high-priority solar system occultation events (e.g., Sicardy et al 2011a;Ortiz et al 2012Ortiz et al , 2017 are also planned using a very high-cadence camera that will be installed at a future date.…”
Section: First Science Results With Minerva-australismentioning
confidence: 99%
“…4. FIRST SCIENCE RESULTS WITH MINERVA-AUSTRALISWhile the primary focus of MINERVA-Australis will be the radial velocity follow-up of transiting planet candidates found by TESS, five secondary photometric science goals include: photometric follow-up of TESS and other transit survey planets to ensure that the ephemerides are up-to-date and accurate for future follow-up observations (e.g.,Hoyer et al 2016;Wang et al 2018b), ruling out potential false positives from…”
mentioning
confidence: 99%